Promosi Kesehatan dalam Pencegahan Nyeri Punggung Bawah pada Kelompok Wanita Tani Sutik Nganggur di Dusun Soko - Putri Na’ima Adawiyah Rahmatullah; Alfia Nor Bella; Maryati Maryati; Veni Fatmawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This community service activity aims to improve knowledge and prevent low back pain (LBP) in order to support productivity among members of the Sutik Nganggur Women Farmers Group, who are also engaged in small-scale food production (UMKM). The program was conducted in Gadingsari Village, Bantul, through health promotion sessions and physiotherapy exercise demonstrations involving 20 participants. Educational materials covered the definition, causes, risk factors, symptoms, ergonomic working postures, and preventive strategies for LBP. Participants also received practical training on stretching exercises and proper body mechanics that could be applied during farming and food production activities. The results indicated a significant improvement in participants’ understanding of LBP prevention and ergonomic practices. Participants demonstrated the ability to perform the recommended exercises correctly and showed increased awareness of maintaining safe working postures in their daily activities. This program is expected to reduce the risk of LBP, improve physical well-being, and enhance work productivity. Furthermore, the activity highlights the importance of integrating health education and physiotherapy interventions into community empowerment programs to support sustainable economic activities and improve occupational health among rural workers.